Elementi fondamentali della dottrina della "Terza Roma".: Riflessioni di un canonista - Coppola, Raffaele (Monitor ecclesiasticus, 2018)
This paper tries to demonstrate the equivalence, not the coincidence, between the secular doctrine of the "Third Rome" and the Catholic theory of a future "publica auctoritas universalis", which the comunis opinio interprets as a possible reform of the Organization of Nations United. Nowadays the symphony between Priesthood and Empire can be related to the principle of loyal collaboration between political and religious Authority.